2013
DOI: 10.1007/s10346-013-0393-5
|View full text |Cite
|
Sign up to set email alerts
|

The application of an innovative inverse model for understanding and predicting landslide movements (Salazie cirque landslides, Reunion Island)

Abstract: International audienceThe prediction of landslide movement acceleration is a complex problem, among others identified for deep-seated landslides, and represents a crucial step for risk assessment. Within the scope of this problem, the objective of this paper is to explore a modelling method that enables the study of landslide function and facilitates displacement predictions based on a limited data set. An inverse modelling approach is proposed for predicting the temporal evolution of landslide movement based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 41 publications
1
46
0
Order By: Relevance
“…The quality of point matching is evaluated from the quality of geometric transformation between of the point clouds identified on both images. showed that a displacement of at least 5 m towards the north occurred during the year that followed this extreme event [30]. Figure 2) showed that a displacement of at least 5 m towards the north occurred during the year that followed this extreme event [30].…”
Section: Methodsmentioning
confidence: 94%
See 4 more Smart Citations
“…The quality of point matching is evaluated from the quality of geometric transformation between of the point clouds identified on both images. showed that a displacement of at least 5 m towards the north occurred during the year that followed this extreme event [30]. Figure 2) showed that a displacement of at least 5 m towards the north occurred during the year that followed this extreme event [30].…”
Section: Methodsmentioning
confidence: 94%
“…showed that a displacement of at least 5 m towards the north occurred during the year that followed this extreme event [30]. Figure 2) showed that a displacement of at least 5 m towards the north occurred during the year that followed this extreme event [30]. Only the south-north component of the displacement measured by DGPS is available.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations